Diagnosis Kesulitan Belajar Matematika Siswa Sekolah Dasar Berdasarkan Perspektif Guru - Wandari, Wily; Amani, Shafira Rizka; Sahara, Sani; Nurcahyono, Novi Andri; Sari, Venna Puspita; Aeni, Maisa Hurul (Jurnal PEKA (Pendidikan Matematika), 2026)
Mathematics learning difficulties in elementary school may arise from conceptual, procedural, linguistic, and affective factors; therefore, teachers' perspectives are essential for identifying the source of errors and selecting responsive support. This study examined teachers' perspectives through three connected foci: diagnosis of learning difficulties, mathematical topics perceived as difficult, and intervention strategies. A descriptive survey with qualitative components involved 31 elementary school and madrasah ibtidaiyah teachers teaching Grades I-VI. The instrument consisted of 24 unique Likert statements and two open-ended questions. Quantitative data were analyzed using descriptive statistics and Cronbach's alpha, while open responses were coded thematically. The overall score was very high (M = 4.38; SD = 0.43; alpha = .965). Affective support and classroom climate obtained the highest mean (M = 4.47), followed by identification and understanding of difficulties (M = 4.38), while instructional strategies and collaboration were relatively lower (M = 4.33). Multiplication-division and fractions-decimals-percentages were the most frequently reported difficult topics. Teachers mainly used concrete or visual representations, scaffolded practice, games, contextual tasks, and individual support. The analysis indicates a relative diagnosis-to-intervention gap: teachers show strong diagnostic awareness and affective support, but differentiated follow-up, family communication, and systematic monitoring require further strengthening. These findings provide an empirical basis for developing a teacher-based diagnostic model for mathematics learning difficulties in elementary schools